Negotiating water rights - Bruns, Bryan Randolph; Meinzen-Dick, Ruth Suseela; International Food Policy Research Institute (New Delhi : Vistaar Publications, 2000)
Outcome of various conferences.
"International Food Policy Research Institute."
Includes bibliographical references and index.
Keywords: Water-supply -- Management -- International cooperation; Watershed management -- International cooperation; Water rights; Conflict management; Water-supply.